An empirical investigation of the determinants of cash Waqf awareness in Malaysia - Adeyemi, Adewale Abideen; Ismail, Nurul Aini; Mohd Hassan, Siti Sabariah (International Islamic University Malaysia, 2016)
Notwithstanding the consensus among most classical and contemporary scholars on the permissibility of cash or money for Waqf purpose, its apparent limited application to religious purposes in Malaysia undermines its potentials for socio-economic development. Extant Malaysia theoretical and conceptual studies only offered remarks on the likely low levels of application of this very important variant of Waqf in Malaysia. Thus a lacuna exists to empirically assess the level of awareness and unravel the likely factors that explain such limited application of Cash Waqf in Malaysia. In an attempt to fill this gap in this study, data elicited from respondents via an adopted survey instrument was subjected to both descriptive and inferential statistical analysis. The results indicated that the awareness level is still low and that social culture, lack of promotion, and lack of understanding statistically and significantly explain the level of awareness and application about Cash Waqf among the respondents. Recommendations contingent on research findings were offered.